Unwanted disorders and xenogeneic graft‐versus‐host disease in experimental immunodeficient mice: How to evaluate and how to report - Seyed Mostafa Monzavi; Samad Muhammadnejad; Vahid Mansouri; Hami Ashraf; Naser Ahmadbeigi (Animal Models and Experimental Medicine)
Abstract Human‐derived tumor models are essential for preclinical development of new anticancer drug entities. Generating animal models bearing tumors of human origin, such as patient‐derived or cell line–derived xenograft tumors, is dependent on immunodeficient strains. Tumor‐bearing immunodeficient mice are susceptible to developing unwanted disorders primarily irrelevant to the tumor nature; and if get involved with such disorders, reliability of the study results will be undermined, inevitably confounding the research in general. Therefore, a rigorous health surveillance and clinical monitoring system, along with the establishment of a strictly controlled barrier facility to maintain a pathogen‐free state, are mandatory. Even if all pathogen control and biosafety measures are followed, there are various noninfectious disorders capable of causing tissue and multiorgan damage in immunodeficient animals. Therefore, the researchers should be aware of sentinel signs to carefully monitor and impartially report them. This review discusses clinical signs of common unwanted disorders in experimental immunodeficient mice, and how to examine and report them.